2008
DOI: 10.1124/mol.108.049189
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Binding Site for the Endogenous Agonist, Small-Molecule Agonists, and Ago-allosteric Modulators on the Ghrelin Receptor

Abstract: A library of robust ghrelin receptor mutants with single substitutions at 22 positions in the main ligand-binding pocket was employed to map binding sites for six different agonists: two peptides (the 28-amino-acid octanoylated endogenous ligand ghrelin and the hexapeptide growth hormone secretagogue GHRP-6) plus four nonpeptide agonists-the original benzolactam L-692,429 [3-amino-3-methyl-N-(2,3,4,5-The strongest mutational effect with respect to decrease in potency for stimulation of inositol phosphate turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 44 publications
7
60
1
Order By: Relevance
“…Together, the results from the reporter and binding assays suggested that the oxime derivatives were bound to the allosteric site of human GLP-2R. It has been speculated that the binding sites of several ago-allosteric modulators overlap with those of the endogenous ligands, for example, ghrelin (13,21). However, it has not been clarified how an agoallosteric modulator binds when its binding site overlaps with that of an orthosteric ligand, although some scenarios have been presented to explain the phenomenon (21).…”
Section: Referencesmentioning
confidence: 94%
“…Together, the results from the reporter and binding assays suggested that the oxime derivatives were bound to the allosteric site of human GLP-2R. It has been speculated that the binding sites of several ago-allosteric modulators overlap with those of the endogenous ligands, for example, ghrelin (13,21). However, it has not been clarified how an agoallosteric modulator binds when its binding site overlaps with that of an orthosteric ligand, although some scenarios have been presented to explain the phenomenon (21).…”
Section: Referencesmentioning
confidence: 94%
“…Previously described agonists for the ghrelin receptor (peptides and non-peptide ligands) are all strongly dependent on GluIII:09 as an anchor point (21,41). For example, the potency of ghrelin itself is decreased 250-fold, and the prototype smallmolecule agonist MK-677 is affected more than 10.000-fold by substitution at this position (Fig.…”
Section: Residues Important For Ghrelin Receptor Agonists In General mentioning
confidence: 99%
“…For example, the potency of ghrelin itself is decreased 250-fold, and the prototype smallmolecule agonist MK-677 is affected more than 10.000-fold by substitution at this position (Fig. 8, A and B) (21,41). GluIII:09 is thought to play a similar role for agonist ligands in the ghrelin receptor as the neighboring classical AspIII:08 does for ligands in general in the monoamine receptor system (42).…”
Section: Residues Important For Ghrelin Receptor Agonists In General mentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the ghrelin receptor is particularly suited because even in the absence of its endogenous agonist, it displays almost 50% of its maximal signaling capacity, and, importantly, the ghrelin receptor is generally robust with respect to mutational changes (20,21).…”
Section: Functional Analysis Of Phevi:09 In the Ghrelin Receptor-mentioning
confidence: 99%